Recent advances in medicinal compounds related to corneal crosslinking - Qin, Danyi; Han, Yi; Wang, Lixiang; Yin, Hongbo (Frontiers in Pharmacology, 2023)
Corneal crosslinking (CXL) is the recognized technique to strengthen corneal collagen fibers through photodynamic reaction, aiming to halt progressive and irregular changes in corneal shape. CXL has greatly changed the treatment for keratoconus (KCN) since it was introduced in the late 1990s. Numerous improvements of CXL have been made during its developing course of more than 20 years. CXL involves quite a lot of materials, including crosslinking agents, enhancers, and supplements. A general summary of existing common crosslinking agents, enhancers, and supplements helps give a more comprehensive picture of CXL. Either innovative use of existing materials or research and development of new materials will further improve the safety, effectiveness, stability, and general applicability of CXL, and finally benefit the patients.